PICTORIAL ART OF EL GRECO : transmaterialities, temporalities, and media - Stoenescu, Livia (Visual and material culture, 1300-1700, 2019)
Frontmatter --Contents --List of Illustrations --Acknowledgments --Introduction --1. Prototypal Images Reaffirmed in Early Modern Painting --2. Spanish Miraculous Images, Sacred Narratives, and Aesthetic Goals --3. El Greco's The Purification of the Temple --4. Reinventing the Nude in an Age of Censorship --5. The Dialogue of Classical and Devotional Cultures in El Greco's Laocoön of Toledo --Bibliography --Index